The Influence of Urbanization, Foreign Direct Investment, and Economic Growth on Environmental Degradation in the OIC Countries - Afifa Luqmannur Rohman; Raditya Sukmana (Jurnal Ekonomi Syariah Teori dan Terapan, 2023)
ABSTRACT This research aims to determine the influence of Urbanization, FDI, and Economic Growth on environmental degradation within the OIC member countries. The CO2 Emission variable is used as an indicator of environmental degradation. The analytical method used in this study uses multiple regression analysis with the EVIEWS 9 application. The sample of this study uses OIC member countries in 1995-2018 with 288 observational data. The results of this study indicate that there is a significant positive influence on the variables Urbanization and Economic Growth on CO2 Emissions. While the FDI variable has an insignificant positive effect on CO2 emissions. The scope of this research is limited by the availability of data which is only in the form of 12 countries out of 57 member countries of the Organization of Islamic Cooperation. Keyword : Urbanization, Foreign Direct Investment, Economic Growth, CO2 Emissions, OIC, Pollution, Environmental Degradation.   ABSTRAK Peneltian ini memiliki tujuan untuk mengetahui pengaruh Urbanisasi, FDI, dan Pertumbuhan Ekonomi memiliki pengaruh terhadap degradasi lingkungan di lingkup negara Anggota OKI. Variabel Emisi CO2 digunakan sebagai gambaran indikator degradasi lingkungan. Metode analisis yang digunakan dalam penelitian ini menggunakan analisis regresi berganda dengan aplikasi EVIEWS 9. Sampel dari penelitian ini menggunakan negara Anggota OKI pada tahun 1995-2018 dengan 288 data observasi. Hasil dari penelitian ini menunjukkan adanya pengaruh signifikan positif pada variabel Urbanisasi dan Pertumbuhan Ekonomi terhadap Emisi CO2. Sedangkan variabel FDI memiliki pengaruh positif tidak signifikan terhadap Emisi CO2. Lingkup penelitian ini terbatasi dengan ketersediaan data yang hanya berupa 12 Negara dari 57 Negara Anggota Organisasi Kerjasama Islam. Kata Kunci : Urbanisasi, Foreign Direct Investment (FDI), Pertumbuhan Ekonomi, Emisi CO2, OKI, Polusi Udara, Degradasi Lingkungan.